2012
DOI: 10.1590/s1517-83822012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Carriage frequency, phenotypic and genotypic characteristics of Staphylococcus aureus isolated from dialysis and kidney tranplant patients at a hosptial in northern Paraná

Abstract: The objective of the present study was to determine the frequency of Staphylococcus aureus nasal carriage among dialysis and kidney transplant patients, to identify the antimicrobial resistance profile of these strains and to verify their genetic profiles with the RW3A primer. The study included 159 individuals, comprising 111 dialysis and 48 kidney transplant patients. Of the 48 transplant patients, 75% were positive for S.aureus, whereas 49% of the 111 dialysis patients were carriers. Two samples yielded con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Two articles (26,31) included overlapping data with references (15) and (19), leaving a total of 23 studies coded from 25 articles (13 studies reported MRSA colonization data and 11 VRE colonization data) ( Figure 1flow chart). Seventeen out of these 23 studies (74%) enrolled liver transplant patients; 2 studies included kidney transplant recipients (12,16), 2 studies included kidney and/ or pancreas transplant recipients (13,27) and 2 included lung transplant recipients (32,33). All studies used culture methods for MRSA and VRE surveillance and were deemed of adequate quality (see Supplementary Appendix) to extract the main outcome measure, namely the colonization rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles (26,31) included overlapping data with references (15) and (19), leaving a total of 23 studies coded from 25 articles (13 studies reported MRSA colonization data and 11 VRE colonization data) ( Figure 1flow chart). Seventeen out of these 23 studies (74%) enrolled liver transplant patients; 2 studies included kidney transplant recipients (12,16), 2 studies included kidney and/ or pancreas transplant recipients (13,27) and 2 included lung transplant recipients (32,33). All studies used culture methods for MRSA and VRE surveillance and were deemed of adequate quality (see Supplementary Appendix) to extract the main outcome measure, namely the colonization rates.…”
Section: Resultsmentioning
confidence: 99%
“…In the postoperative screening, the estimated MRSA colonization was derived from six studies (12)(13)(14)(15)21,32) with 2342 patients (three on liver transplant recipients, one on lung recipients, one on kidney and one on kidney and/or pancreas) and it was 9.4% (95% CI 3.0-18.5; t 2 ¼ 0.096) and across eight VRE studies (14,(16)(17)(18)20,27,30,36) with 1369 patients (six on liver transplant recipients, one on kidney and one on kidney and/or pancreas), colonization was 16.2% (95% CI 10.7-22.6); t 2 ¼ 0.051. There was no evidence of publication bias for MRSA (Egger's bias ¼ 7.15, p ¼ 0.16), or VRE (Egger's bias ¼ 1.12, p ¼ 0.76).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study concluded that the correlation between antimicrobial resistance and the dissemination of clonal groups of S. aureus is an important tool during outbreaks or in endemic areas [47].…”
Section: Discussionmentioning
confidence: 99%
“…This result was presented in a study of 159 patients in which nasal samples were collected from patients who had undergone kidney transplant or who were undertaking dialysis. Nasal colonization of S.aureus was found in 75% (36/48) of the transplant patients and in 49% (55/111) of dialysis patients, highlighting the need for prevention and control measures in this group of patients (27) .…”
Section: Discussionmentioning
confidence: 99%